EAACI Biologicals Guidelines—Recommendations for severe asthma. Issue 1 (10th August 2020) - Agache, Ioana; Akdis, Cezmi A.; Akdis, Mubeccel; Canonica, Giorgio Walter; Casale, Thomas; Chivato, Tomas; Corren, Jonathan; Chu, Derek K.; Del Giacco, Stefano; Eiwegger, Thomas; Flood, Breda; Firinu, Davide; et al.
Abstract: Severe asthma imposes a significant burden on patients, families and healthcare systems. Management is difficult, due to disease heterogeneity, co‐morbidities, complexity in care pathways and differences between national or regional healthcare systems. Better understanding of the mechanisms has enabled a stratified approach to the management of severe asthma, supporting the use of targeted treatments with biologicals. However, there are still many issues that require further clarification. These include selection of a certain biological (as they all target overlapping disease phenotypes), the definition of response, strategies to enhance the responder rate, the duration of treatment and its regimen (in the clinic or home‐based) and its cost‐effectiveness. The EAACI Guidelines on the use of biologicals in severe asthma follow the GRADE approach in formulating recommendations for each biological and each outcome. In addition, a management algorithm for the use of biologicals in the clinic is proposed, together with future approaches and research priorities.